2017
DOI: 10.1177/1747493017730779
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical characteristics of the styloid process in internal carotid artery dissection: Case–control study

Abstract: Introduction Pathophysiology of cervical artery dissection is complex and poorly understood. In addition to well-known causative and predisposing factors, including major trauma and monogenic connective tissue disorders, morphological characteristics of the styloid process have been recently recognized as a possible risk factor for cervical internal carotid artery dissection. Aims To study the association of the anatomical characteristics of styloid process with internal carotid artery dissection. Methods Retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Located between the ICA and the external carotid artery, the distal end of the SP extends inwards, forwards, and downwards (10,11). As shown in our current study, ultrasound could clearly reveal the positional relationship between the SP and blood vessels in the neck.…”
Section: Discussionsupporting
confidence: 69%
“…Located between the ICA and the external carotid artery, the distal end of the SP extends inwards, forwards, and downwards (10,11). As shown in our current study, ultrasound could clearly reveal the positional relationship between the SP and blood vessels in the neck.…”
Section: Discussionsupporting
confidence: 69%
“…3 Sixty-one percent of CeAD is spontaneous (sCeAD), occurring without trauma. 4 Many studies investigated the etiology and risk factors of sCeAD, and identified numerous genetic and environmental factors including α1-antitrypsin deficiency, 5 hyperhomocystinemia, [6][7][8] recent infection, 9,10 styloid process length [11][12][13] or its proximity to the hyoid bone, 14 arterial tortuosity, [15][16][17] and connective tissue disorders. 18,19 However, cardiovascular risk factors such as smoking, hypertension, and diabetes were less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Three muscles are attached to SP, namely the stylopharnygeous, stylohyoid and styloglossal muscles, in addition to the stylohyoid and stylomandibular ligaments. Anatomically, it has an intimate close contact with the upper portion of carotid space and its contents, including the cranial nerves V, IX (1). Its normal length ranges between 20-30 mm; however, it shows variation among different people (2).…”
Section: Introductionmentioning
confidence: 99%